2014
DOI: 10.1039/c4tb00852a
|View full text |Cite
|
Sign up to set email alerts
|

Glycopolymer-coated iron oxide nanoparticles: shape-controlled synthesis and cellular uptake

Abstract: Serum-stable glyco-nanoparticles with controlled shape were easily obtained and exhibit shape-dependent cell uptake behaviors as well as enhanced activity toward specific lectins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 52 publications
1
32
0
Order By: Relevance
“…[1][2][3] Uptake of engineered nanoparticles into cells tends to be size, shape and charge-dependent. 2,4,5 The properties of surface materials are also of importance for the targeted delivery of particles into specific cells, or even defined organelles. 5,6 Immobilization of carbohydrates, especially glycopolymers, onto magnetic or fluorescent nanoparticles has previously been exploited for pathogen detection and cell imaging.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Uptake of engineered nanoparticles into cells tends to be size, shape and charge-dependent. 2,4,5 The properties of surface materials are also of importance for the targeted delivery of particles into specific cells, or even defined organelles. 5,6 Immobilization of carbohydrates, especially glycopolymers, onto magnetic or fluorescent nanoparticles has previously been exploited for pathogen detection and cell imaging.…”
Section: Introductionmentioning
confidence: 99%
“…8B) Compared to their spherical counterparts, capsules with an ellipsoidal or other non-spherical shape have many additional advantages such as enhanced cargo loading efficiency for drug delivering, improved cell uptake in the cases of cancer treatment and enhanced packing efficiency in solid materials as indicated by previous works. [13][14][15] Relative to the current work, we think the advantage of enhanced packing efficiency in solid materials is very benecial. In the format of dried powders in which particles are randomly packed, ellipsoidal particles can randomly pack more densely and achieve a volume fraction (4) up to 0.74, higher than 0.64 of spherical ones.…”
Section: 33mentioning
confidence: 99%
“…5,6,[8][9][10][11][12] It is noted that most of PDA capsules prepared so far have a spherical shape, [4][5][6][7]11 while non-spherical ones may have additional advantages in cargo loading, cell uptake and enhanced packing efficiency in energetic materials. [13][14][15] However, preparation of non-spherical polymeric capsules is generally challenging.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure A, the addition of ConA to CpG‐GM@AuNPs decorated with mannose and glucose gave rise to aggregation in PBS. Notably, in case of CpG‐G@AuNPs, obvious aggregation was not observed (Figure B) due to the relatively weak binding ability in PBS, which indicated that the CpG‐GM@AuNPs are attractive candidates for specific targeting to APCs. In fact, antigen and adjuvant internalization by APCs is important for the efficacy of vaccines.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the cell uptake of glycoadjuvant@AuNPs by APCs, Raw 264.7 macrophages were incubated with CpG‐GM@AuNPs or CpG‐G@AuNPs. The number of NPs ( N ) uptaken per cell can be calculated using inductively coupled plasma‐atomic emission spectroscopy (ICP‐AES) technique . As shown in Figure D, compared to CpG‐G@AuNPs, DC‐targeting CpG‐GM@AuNPs showed significantly enhanced cell uptake by macrophages.…”
Section: Methodsmentioning
confidence: 99%